Pharmacological functions of salidroside in renal diseases: facts and perspectives - Liu, Qiong; Chen, Jianzhu; Zeng, Anqi; Song, Linjiang (Frontiers in Pharmacology, 2024)
Rhodiola rosea is a valuable functional medicinal plant widely utilized in China and other Asian countries for its anti-fatigue, anti-aging, and altitude sickness prevention properties. Salidroside, a most active constituent derived from Rhodiola rosea, exhibits potent antioxidative, hypoxia-resistant, anti-inflammatory, anticancer, and anti-aging effects that have garnered significant attention. The appreciation of the pharmacological role of salidroside has burgeoned over the last decade, making it a beneficial option for the prevention and treatment of multiple diseases, including atherosclerosis, Alzheimer's disease, Parkinson's disease, cardiovascular disease, and more. With its anti-aging and renoprotective effects, in parallel with the inhibition of oxidative stress and inflammation, salidroside holds promise as a potential therapeutic agent for kidney damage. This article provides an overview of the microinflammatory state in kidney disease and discuss the current therapeutic strategies, with a particular focus on highlighting the recent advancements in utilizing salidroside for renal disease. The potential mechanisms of action of salidroside are primarily associated with the regulation of gene and protein expression in glomerular endothelial cells, podocytes, renal tubule cells, renal mesangial cells and renal cell carcinoma cell, including TNF-α, TGF-β, IL-1β, IL-17A, IL-6, MCP-1, Bcl-2, VEGF, ECM protein, caspase-3, HIF-1α, BIM, as well as the modulation of AMPK/SIRT1, Nrf2/HO-1, Sirt1/PGC-1α, ROS/Src/Cav-1, Akt/GSK-3β, TXNIP-NLRP3, ERK1/2, TGF-β1/Smad2/3, PI3K/Akt, Wnt1/Wnt3a β-catenin, TLR4/NF-κB, MAPK, JAK2/STAT3, SIRT1/Nrf2 pathways. To the best of our knowledge, this review is the first to comprehensively cover the protective effects of salidroside on diverse renal diseases, and suggests that salidroside has great potential to be developed as a drug for the prevention and treatment of metabolic syndrome, cardiovascular and cerebrovascular diseases and renal complications.